Key professional stakeholders roles in promoting older people's autonomy in residential care - Moilanen, Tanja; Suhonen, Riitta; Kangasniemi, Mari (Sage, 2025)
Background: Older people's autonomy is an ethical and legal principle in everyday residential care, but there is a lack of clarity about the roles and responsibilities of the key professional stakeholder groups involved.
Research objectives: This study aimed to identify and define the roles and responsibilities of the key professional stakeholder groups involved in promoting older people's autonomy in residential care settings.
Research design: We used a Delphi method with two iterative rounds of online group discussions and collected data from experts in older people's care in Finland in summer 2020. The data were analyzed using deductive-inductive content analysis methods.
Ethical considerations: According to Finnish legislation, this type of research did not need approval from a research ethics committee. Informed consent from the participants was obtained and they were informed about the voluntary nature and confidentiality of the study and their right to withdraw at any time.
Results: Key professional stakeholders had different roles and responsibilities, but their shared, integrated goal was to achieve older people's autonomy in residential care settings. Their combined roles and responsibilities covered all aspects of promoting older people's autonomy, from care and service planning and daily decision-making to service structures that included ethical competencies and monitoring. Multipronged, variable, coordinated strategies were required to identify, assess, and promote autonomy at different levels of care.
Conclusion: Key professional stakeholders need to work together to provide an unbroken chain of care that provides older people with autonomy in residential care settings. In future, more knowledge is needed about how to create structures to achieve the shared goal of older people's autonomy in these settings.